Rethinking Women’s Studies: Curriculum, Pedagogy, and the Introductory Course - Hobbs, Margaret; Rice, Carla (Atlantis, 2012)
We comment on the current context framing women’s and gender studies in Canada, identify recent and important curricular trends, and discuss some guiding principles that we have used to revise our first-year course. We offer reflections that might assist instructors in the challenging task of mounting the entry level course.